KOMPENSASI FINANSIAL DAN KOMPENSASI NON FINANSIAL TERHADAP KINERJA KARYAWAN - -, Musafir (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
Abstract: This research was aimed to find out and analyze the effect of compensation in form of financial and non financial partially and simultaseously on the employees performance at PT. Gorontalo Fitrah mandiri. The sampling tecnhnique taken was through proportionate stratified random sampling, covering 42 respondents. The primary data were conducted by using a questionnaire previously examined to see the validity and reliability of each item. The method of analysis employed in this research was path analysis. The result of the research showed that the compensations covering financial and non financial simultaneously affected on the employeesâ performance indicated positive and significant by a determinant coeficient 52.59%. The solid correlation between the compensation and the performance was categorized high. The financial and non financial compensations psitively and significantly affected on the employeesâ performance at PT. Gorontalo Fitrah Mandiri, even though, both simultant and partial effects were considered low. Key words: compensation financial,Â  compensation non financial,Â  employees performance